Strategi Public Relations Kedai Kopi dalam Memperbaiki Reputasi di Tengah Isu Boikot - Martin, Edbert; Setyanto, Yugih (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2025)
Kedai Kopi Indonesia, as a subsidiary of a global coffee shop giant, faces challenges in maintaining a positive image amid sensitive social and political issues. This research examines Kedai Kopi Indonesia's strategic public relations approach in dealing with controversy, improving brand perception, and building customer loyalty. By utilising open communication, professionalism and responsiveness, Kedai Kopi Indonesia was able to navigate sensitive issues such as political statements or social movements. The company also emphasises inclusivity, diversity, and sustainability in their campaigns to strengthen relationships with local communities. Through the use of social media and corporate social responsibility programmes, Kedai Kopi engages with audiences to mitigate the negative impact of public criticism. This article highlights the key elements of Kedai Kopi Indonesia's PR strategy, showing how they managed the crisis while adhering to their core values and ensuring long-term success in the Indonesian market. With this approach, Kedai Kopi was not only able to overcome challenges but also carved out a positive image that became stronger in the eyes of the Indonesian public. Kedai Kopi Indonesia, sebagai anak perusahaan dari raksasa kedai kopi global, menghadapi tantangan dalam mempertahankan citra positif di tengah isu sosial dan politik yang sensitif. Penelitian ini mengkaji pendekatan strategis Public Relations Kedai Kopi Indonesia dalam menghadapi kontroversi, meningkatkan persepsi merek, dan membangun loyalitas pelanggan. Dengan memanfaatkan komunikasi terbuka, profesionalisme, dan responsif, Kedai Kopi Indonesia dapat menavigasi isu-isu sensitif seperti pernyataan politik atau gerakan sosial. Perusahaan ini juga menekankan inklusivitas, keberagaman, dan keberlanjutan dalam kampanye mereka untuk memperkuat hubungan dengan komunitas lokal. Melalui penggunaan media sosial dan program tanggung jawab sosial perusahaan, Kedai Kopi berinteraksi dengan audiens untuk mengurangi dampak negatif dari kritik publik. Artikel ini menyoroti elemen-elemen kunci dari strategi PR Kedai Kopi Indonesia, menunjukkan bagaimana mereka mengelola krisis sembari mengikuti nilai inti, serta memastikan kesuksesan jangka panjang di pasar Indonesia. Dengan pendekatan tersebut, Kedai Kopi tidak hanya mampu mengatasi tantangan, tetapi juga mengukir citra positif yang semakin kuat di mata masyarakat Indonesia.